Advancing the public health applications of Chlamydia trachomatis serology. Issue 12 (December 2018) - Woodhall, Sarah C; Gorwitz, Rachel J; Migchelsen, Stephanie J; Gottlieb, Sami L; Horner, Patrick J; Geisler, William M; Winstanley, Catherine; Hufnagel, Katrin; Waterboer, Tim; Martin, Diana L; Huston, Wilhelmina M; Gaydos, Charlotte A; et al.
Summary: Genital Chlamydia trachomatis infection is the most commonly diagnosed sexually transmitted infection. Trachoma is caused by ocular infection with C trachomatis and is the leading infectious cause of blindness worldwide. New serological assays for C trachomatis could facilitate improved understanding of C trachomatis epidemiology and prevention. C trachomatis serology offers a means of investigating the incidence of chlamydia infection and might be developed as a biomarker of scarring sequelae, such as pelvic inflammatory disease. Therefore, serological assays have potential as epidemiological tools to quantify unmet need, inform service planning, evaluate interventions including screening and treatment, and to assess new vaccine candidates. However, questions about the performance characteristics and interpretation of C trachomatis serological assays remain, which must be addressed to advance development within this field. In this Personal View, we explore the available information about C trachomatis serology and propose several priority actions. These actions involve development of target product profiles to guide assay selection and assessment across multiple applications and populations, establishment of a serum bank to facilitate assay development and evaluation, and development of technical and statistical methods for assay evaluation and analysis of serological findings. The field of C trachomatis serology will benefit from collaboration across the public health community to align technological developments with their potential applications.